Islamic Identity Crisis in White Teeth (2000) by Zadie Smith - LOUAFI, Habib (My University, 2020)
The diversity of cultures existing in the world had created a dynamic society which is known as a multicultural society. It had engulfed different cultures within in one society. However, the development of multicultural society was not sufficient to the harmony of society, in such a manner, intercultural society was introduced to the mass. The Muslims living in those societies experienced identity loss and deconstruction due unsuitable governmental policies and subjective representation against Islam. In this context, White Teeth (2000) by Zadie Smith explores how Muslims immigrants are influenced by the nature of these multicultural and intercultural societies and their policies. The methodology used in this work is mainly descriptive and analytical concentrating on the novel at hand and the document relating the theme of study. The work hereby is composed of three chapters, whereby the first overviews both multicultural, intercultural societies, and the discussion of identity; and second chapter, reveals how Islam originated in Britain and how it is represented to the British population and the world, discussing as well the concepts of multi-faith and freedom and draw link between integration and assimilation and their effect upon Islamic identity construction; in third chapter, the work aimed in analyzing Muslims characters in the novel and how they constructed their identity in these societies. In the end, the analysis has revealed that the adopted policies and the existence do affect in the construction of Islamic identity on two folds, one is direct impact where they are supposed to dissolve inside a melting pot, and the other is indirect influence where it causes either for mental or physical discrimination that led the characters to abandon their identity and compromise it for the sake of existence in the societies. Based on the research’s result, the dissertation conclude that the multicultural novel White Teeth by Zadie Smith is an attempt to denounce the idea of third place and raise an awareness on the struggle immigrants face every day in these societies with their policies.
Keywords: Britain; Islam; Mulim immigrants; White Teeth by Zadie Smith; Multicultural; Intercultural; Policy; Study and analysis